2015
DOI: 10.15587/2313-8416.2015.56682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wheat-rye translocations 1AL/1RS AND 1ВL/1RS on the elements of productivity in f1 winter bread wheat

Abstract: Виявлена значна відмінність між гібридами першого покоління за повторюваністю прояву елементів продуктивності колосу. Спостерігається тенденція щодо прояву наддомінування в гібридів, у яких одна з батьківських форм містить у своєму генотипі 1BL/1RS або 1AL/1RS транслокацію. Успадкування елементів продуктивності відбувається за типами: наддомінування, часткове позитивне домінування, проміжне успадкування, часткове від'ємне успадкування, депресія Ключові слова: пшениця озима, гібридні комбінації, пшенично-житні … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The main guarantee for the creation of modern high-productive, adaptive varieties, of course, is the base line. Breeding practice confirms the need for focused search for valuable parental forms among the world's plant diversity (Bakumenko et al, 2015). The historical experience of mankind has shown that a prerequisite for the effective development of agriculture, science and education in any country is the wide utilization and testing of valuable samples of foreign plant genes (Lytvynenko & Topal, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main guarantee for the creation of modern high-productive, adaptive varieties, of course, is the base line. Breeding practice confirms the need for focused search for valuable parental forms among the world's plant diversity (Bakumenko et al, 2015). The historical experience of mankind has shown that a prerequisite for the effective development of agriculture, science and education in any country is the wide utilization and testing of valuable samples of foreign plant genes (Lytvynenko & Topal, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One of the genes that provide resistance to the TTKSK race of stem rust is the SrA1R gene, which is on the rye 1AL/1RS translocation from Amigo. It is designated Sr1RSAmigo (Kozub et al, 2010;Olson et al, 2010;Bakumenko et al, 2015). It is this translocation that contains the resistance gene to powdery mildew PM17, which made it possible to hypothesize the resistance of the obtained samples simultaneously to two diseases of stem rust and powdery mildew.…”
Section: Introductionmentioning
confidence: 99%